A new species of Simopelta (Hymenoptera: Formicidae: Ponerinae) from Brazil and Costa Rica - Fernandes, Itanna O.; Souza, Jorge L. P.; Fernández C., Fernando; Delabie, Jacques H. C.; Schultz, Ted R. (Zootaxa, 2015)
The genus Simopelta consists of 21 described species restricted to Central America and South America. The present study describes a new cryptobiotic species, Simopelta anomma sp. nov.. The new species is blind, possesses a 3-segmented antennal club, and has the midtibia with several stout setae, a combination of characters unique within the genus. Moreover, some traits of this species require broadening the definition of the genus. The discovery of S. anomma sp. nov. suggests that many undiscovered species, some of which may be important for understanding ant evolution, remain hidden below ground in Neotropical rainforests.